Advanced control of wind power systems - Dang, Dinh Quy (2012)
Wind power system control especially for variable speed operation of wind turbine has been carried out in several decades; and the research activities are still on-going with more concern recently. The reason is that a variable speed wind power system produces higher electrical energy and power efficiency than a conventional wind power plant. However, the variance of rotor speed leads to the changes of working conditions in accordance with stochastic wind profiles. The different control objectives for each working condition are also addressed as a problem of controller design. Beyond the multiple operating regions, wind power system control has to deal with the nonlinearity of wind torque and the stochastic behavior of wind. Hence, the control system is further complicated.